The Relationship Between the Role of Health Workers, Family Support, Social Support with Family Caregiver in Caring People with Mental Disorders in Kediri Regency - Agustin Widyowati; Bhisma Murti; Aris Sudiyanto; Suminah (LPPM Universitas Duta Bangsa Surakarta, 2021)
Recurrence of mental disorders contributes for the highest disability burden. The frequency of recurrence will decrease after the involvement/support of the caregiver. However, the caregiver will experience a heavy burden in caring for sufferers so that they need support in caring for people with mental disorders. The purpose of this study was to analyze the relationship between the role of health workers, family support, social support, and family caregivers in caring for people with mental disorders in the Kediri Regency. This research was conducted in Kediri Regency using a cross-sectional approach. The population of all family caregivers with mental disorders was 76 respondents using the multistage random sampling technique. This study's variables are family support, the role of health workers, social support, and family caregivers. The analysis test used a logistic regression test with the help of SPSS. The results of the family caregiver study had a relationship with the role of health workers (OR = 2.92; 95% CI = 2.59 to 132.65; p = 0.004), family support (OR = 2.55; 95% CI = 2.99 up to 54.97; p = 0.100) , social support (OR = 2.33; 95% CI = 2.17 to 48.82; p = 0.003) . Family caregivers in caring for people with mental disorders can be influenced by health workers, family support, social support. Therefore, it is recommended that health workers be able to provide psychoeducation to both families and communities.